Technical Theatre Practicum - Boltz, Christopher R (Open textbook library., 2019)
Welcome to the exciting world of technical theatre. Studying this topic can lead to many different careers in several different sectors of the economy. The general skills needed for any of the careers or sectors have many things in common. Workers need to be dead-line oriented, as most productions have firm timelines that cannot be altered. Critical thinking and analysis are much needed skills. Almost every project in the field is unique and technicians and designers alike must discover the best way of reaching a project’s goal. Creative problem solving is trait successful practitioners have in common. With every project being unique, there are no guaranteed solutions to the problems that are presented. Technicians draw on their vast experience of what worked in the past that can be adapted to be a solution to the current problems. Clear communication and collaboration round out the necessary skills. No technical theatre project is ever handled by one person on their own. Collaboration with many people is the norm, and successful collaboration requires clear written and verbal communication skills.